Synthesis and biological activities of diarylpentanoids and their pyrazoline analogues / Mohd Fadhlizil Fasihi Mohd Aluwi - Mohd Aluwi, Mohd Fadhlizil Fasihi (2010)
Diarylpentanoid is structurally similar to curcumin 3, a constituent of the rhizome of Curcuma longa L. (turmeric) which is known to possess various pharmaceutical properties. Interestingly diarylpentanoids have been reported to be more active than curcumin. They are also precursors towards the synthesis of nitrogencontaining five-membered heterocyclic compounds called pyrazoline which are reported to possess important pharmacological activities. In this study, 13 diarylpentanoids were successfully synthesized by the reaction between various substituted benzaldehyde with cyclic ketone in the presence of base (NaOH) in EtOH via microwave-assisted (73-92% in 10-60 s) and conventional methods (17-90% in 30-120 min) through Claisen-Schmidt reaction (cross aldol condensation). Microwave-assisted method has been found to be a very efficient method which dramatically reduces reaction time and significantly improved yields as compared to conventional method. Diarylpentanoids 43 and 49 were selected as representatives of precursor bearing electron-withdrawing and electron-donating group, respectively in the synthesis of their pyrazoline analogues. Compound 64 and 65 were obtained in 87-99% using microwave-assisted method. In all reactions, it was found that compounds bearing halogen substituents undergo reaction at a faster rate than those bearing methoxy substituents. Compounds 43, 49, 64 and 65 were evaluated for their anti-inflammatory potential with Griess assay and their immunomodulatory potential by employing the T cell proliferation and chemiluminescence assays. In the Griess assay, only compound 65 was found to increase the inhibition of nitric oxide (NO) production of macrophages (RAW 264.7 cell lines) from 5.80-28.97% (with respect to compound 49) while compound 43 was found to induce the NO production. Pyrazoline analogues 64 and 65 were found to increase the suppression of T cell proliferation as compared to the precursors 43 and 49 from 50.40-96.30% and 18.10-98.30%, respectively. Compounds 64 and 65 also increase the inhibition of reactive oxygen species (ROS) production in human blood from 8.70-28.10 % and 9.50-31.50 %, respectively.